Awareness of parents of special children enrolled in the center for developmental intervention foundation on caries preventive measures - Cheng, Jamie Anne S.
The aim of the study was to assess the awareness of parents of special children enrolled in The Center for Developmental Intervention for school year 1998-1999 on caries preventive measures. Specifically, the study aimed to determine the caries prevention practice of the respondents. The acceptability of a Caries Prevention Program to be started in the school was also assessed. The data were gathered by a questionnaire received through the school and phone call interviews from 50 subjects randomly sampled. To eliminate sampling error 7 subjects were not considered for inadequate answers in the questionnaire. Out of the 43 subjects, 96% are aware of dental prophylaxis and 39% regularly bring their child to the dentist for the procedure; 46% are aware of Topical Fluoride application and 55% have children who had the procedure done on them; 32% are aware of pit and fissure sealants and 46% have children with it. All subjects agree that toothbrushing is an important preventive measure against caries and 93% correspondingly supervise their child's toothbrushing. Ninety-five percent of the subjects want a Caries Prevention Program started in the school. Parents, though not in totality, are aware of caries preventive measures. The dentist is a primary source of awareness for most of the parents. A Caries Prevention Program may be feasible for the school.